2010
DOI: 10.1159/000322040
|View full text |Cite
|
Sign up to set email alerts
|

Impact of <i>gsp</i> Oncogene on the mRNA Content for Somatostatin and Dopamine Receptors in Human Somatotropinomas

Abstract: Introduction: It has been reported in some series that gsp+ somatotropinomas are more sensitive to somatostatin analogues (SA) and dopamine’s actions which may be related to their somatostatin receptor (SSTR) and dopamine receptor (DR) profile. No previous studies have been undertaken to evaluate the SSTR and DR profile related with the gsp status in somatotropinomas. Objectives: To determine if (1) gsp status is correlated with response to octreotide LAR (LAR) and tumor expression patterns of SSTR1-5 and DR1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 90 publications
(88 reference statements)
1
17
0
Order By: Relevance
“…Toboada et al reported that elevated tumor expression of SSTR1, SSTR2, and dopamine receptor 2 may help improve responsiveness to SSA in somatotropinomas. 45 In other study of 21 advanced well-differentiated pancreatic neuroendocrine carcinoma treated with SSA, there was no significant association between expression of SSTR2 or SSTR5, and patient survival. 46 …”
Section: Discussionmentioning
confidence: 88%
“…Toboada et al reported that elevated tumor expression of SSTR1, SSTR2, and dopamine receptor 2 may help improve responsiveness to SSA in somatotropinomas. 45 In other study of 21 advanced well-differentiated pancreatic neuroendocrine carcinoma treated with SSA, there was no significant association between expression of SSTR2 or SSTR5, and patient survival. 46 …”
Section: Discussionmentioning
confidence: 88%
“…None of the patients belongs to pituitary adenoma kindred. In acromegalic patients, only 3 patients were treated with octreotide-LAR before surgery, and prevalence of GNAS oncogene was 10% [15]. In line with this last point, we have previously reviewed [16] that the prevalence of the GNAS oncogene in somatotropinomas is approximately 40%; however it has been shown that this prevalence dramatically varies between studies (ranging from 4.4 to 55%) considering previous series from several countries.…”
Section: Methodsmentioning
confidence: 91%
“…For in vivo studies, we used a set of 74 pituitary samples (66 pituitary adenomas and 8 normal pituitaries; Tables 1–3), in which demographic/clinical data of patients, profile of sst1-5, and presence of GNAS oncogene in somatotropinomas were previously characterized [13,15]. Briefly, somatotropinoma (n = 36; median age: 38 years old; Table 1) and NFPA (n = 30; median age: 51 years old; Table 2) samples were obtained during transsphenoidal surgery of pituitary adenoma (PA) tumors.…”
Section: Methodsmentioning
confidence: 99%
“…The implication of gsp mutation in SSA response has been widely discussed (Larkin et al 2013); nevertheless, a recent meta-analysis revealed that GNAS-positive patients have an approximately 10% greater reduction in GH levels in response to an acute octreotide suppression test (Efstathiadou et al 2015). Additionally, GNAS positive patients show high levels of SSTR2 mRNA (Taboada et al 2011) and low levels of sst5TMD4 .…”
Section: Gnas Mutationmentioning
confidence: 99%